Isolation, in vitro Evaluation, and Molecular Docking Analysis of a Bioactive Phenylpropanoid from Syzygium jambos with Antioxidant and Anticancer Potential against IMR-32 Neuroblastoma Cells (Asian Journal of Pharmaceutics (AJP), 2025)
Neuroblastoma is a highly aggressive pediatric cancer with limited treatment options and a meagerprognosis in advanced stages. Plant-derived natural products represent a valuable source of novel anticancer agents.Syzygium jambos (L.) Alston, traditionally used in folk medicine, has been reported to contain bioactive phenolics,but its anticancer potential remains underexplored. Objective: This study aimed to isolate and characterize bioactivecompounds from S. jambos leaves and evaluate their cytotoxic potential against human neuroblastoma infant mortalityrat (IMR)-32 cells. Materials and Methods: Leaves of S. jambos were sequentially extracted with solvents of increasingpolarity, and extracts were screened for antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The ethanolextract, which showed the highest radical scavenging activity, was subjected to bioassay-guided fractionation by Thin-layer chromatography and silica gel column chromatography. Fractions were tested for antioxidant and cytotoxic activity,and the most active fraction was structurally characterized by spectroscopic and chromatographic methods. Cytotoxicityagainst IMR-32 cells was evaluated by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide)assay, intracellular reactive oxygen species (ROS) levels were measured, and Western Blotting was used to assessapoptosis- and survival-related proteins. In silico molecular docking and ADME analysis were performed to explore themechanism and drug-likeness. Results: The ethanol extract of S. jambos leaves showed strong antioxidant activity, withSyzygium jambos Ethanol fracion (SJEF-16) exhibiting 75.25% DPPH inhibition at 500 μg/mL and an IC50 of 40.93 μg/mL. SJEF-16 decreased IMR-32 neuroblastoma cell viability in a dose-dependent manner, with an IC50 of 28.92 μg/mL, reduced intracellular ROS levels, and moderately downregulated EGFR expression (66.2% of control). Moleculardocking revealed a binding affinity of −6.2 kcal/mol with neuroblastoma-related targets, and ADME analysis predictedgood oral bioavailability (bioavailability score = 0.55). These findings suggest SJEF-16 as a promising antioxidant andanticancer agent. Conclusion: This study reports, for the 1st time, the isolation of (2E)-3-(3-Methoxyphenyl)-2-propen-1-ol from S. jambos leaves with potent cytotoxic and antioxidant activity against neuroblastoma cells. These findingshighlight its potential as a promising lead compound for the development of plant-derived therapeutics against pediatricneuroblastoma